Effect of sowing and plant spacing on pigeonpea (Cajanus cajan) for higher productivity and profitability in India - SEPAT, SEEMA; RAJE, R S; PATIAL, MADHU; SINGH, VICKY; SINGH, G; G, RAMA PRASHAT (The Indian Journal of Agricultural Sciences, 2021)
An experiment was conducted at the research farm of the Indian Agricultural Research Institute, New Delhi during 2016–17. The study was carried out in split-plot design having three dates of sowing (5 June, 21 June and 10 July) in main plot, and spacing (15 cm × 15 cm; 30 cm × 15 cm and 45 cm × 15 cm) in sub-plots with four replications. Results indicated that pigeonpea [Cajanus cajan (L.) Millsp.] sowing on 5 June and 21 June recorded significantly (P>0.05) higher no. of pods/plant in 2016–17. Pigeonpea sowing on 5 June and 21 June recorded higher seed and stalk yield followed by 10 July. Pigeonpea sowing on 5 June recorded higher gross and net returns (86.75 and 54.75 × 103 `/ha, respectively). At flowering stage, leaf litter and root volume were recorded highest with the plant spacing at 45 cm × 15 cm (3.5 kg/ha and 2.85, respectively) in both years. Plant spacing at 45 cm × 15 cm recorded higher seed, stalk and biological yield followed by plant spacing at 35 cm × 15 cm and 15 cm × 15 cm. The gross returns and net returns were recorded higher with plant spacing at 45 cm × 15 cm (89 and 59 × 103 `/ha, respectively). Overall, it can be concluded that pusa arhar-16 can be sown from 5–21 June with plant spacing at 45 cm × 15 cm without any yield penalty in Indo-Gangetic Plains of India.